KARAKTERISTIK USAHATANI CABAI RAWIT DI DUSUN TANGGULUN DESA LAMONGAN KECAMATAN ARJASA KABUPATEN SITUBONDO - Andi Wirawan Setiady; Bambang Suyadi; Titin Kartini (JURNAL PENDIDIKAN EKONOMI: Jurnal Ilmiah Ilmu Pendidikan, Ilmu Ekonomi dan Ilmu Sosial, 2017)
This study aims to examine more deeply about the characteristics of chili farming system in Dusun Tanggulun Lamongan Village Arjasa District Situbondo Regency in the management of land, capital, and labor. Type of research used in this research is descriptive with qualitative approach. Determination of research location determined by Purposive Area method, that is done intentionally by researcher, that is in Dusun Tanggulun Desa Lamongan Arjasa Sub-District Situbondo Regency. The main informants in this study were 5 chili pepper farmers and 9 supporting informants were 5 wives from main informants and 4 farm laborers. Data collection methods used by researchers include interview methods, observation methods, and document methods. Data analysis used in this research consists of several stages, namely data reduction phase, data presentation stage and conclusion drawing stage. The results showed that the chili farmers use the land in the cayenne pepper farm with a semicircular shape that extends or called the bedengan plastic mulch covered. Majority of the main informants use land in the form of beds with mulch plastic covered, the capital is used to buy manure, Urea, ZA, TSP, KCI, Leaf fertilizer, Lime, Plastic mulch, Polibag, Bamboo, Pesticide, and pay land-making farm workers, Pickers of cayenne pepper, as well as using labor from within the family and from outside the family.